Circulating T cells to infliximab are detectable mainly in treated patients developing anti-drug antibodies and hypersensitivity reactions. (26th October 2016) - Vultaggio, A; Petroni, G; Pratesi, S; Nencini, F; Cammelli, D; Milla, M; Prignano, F; Annese, V; Romagnani, S; Maggi, E; Matucci, A; ,
Summary: Antibodies recognizing infliximab (IFX) may develop in a proportion of treated patients, leading to loss of response or hypersensitivity reactions (HRs). T cell response to IFX has been poorly investigated. This paper was addressed to detect IFX-specific T cells in treated patients with inflammatory diseases developing, or not, anti-drug antibodies (ADA) and to correlate the presence of specific T cells with the clinical outcomes of the treatment. A co-culture system of IFX-loaded dendritic cells and purified autologous CD4 + T cells was used to detect memory T cells in 32 ADA + and 39 ADA – IFX-treated patients and control groups. The cytokine profile of IFX-specific T cells was also studied in culture supernatants. IFX-specific cell proliferation was detected mainly in cells from ADA + patients, irrespective of their different diseases. HR patients displayed higher T cell proliferation than non-responder and tolerant patients. A mixed [interferon (IFN)-γ, interleukin (IL)-13, IL-10] cytokine profile was shown in cells from ADA + patients, while IL-10 was the most frequently detected cytokine in the supernatants of cultures from ADA- patients. Immunoglobulin (Ig)E + ADA + patients with previous HRs exhibited a more pronounced type 2 profile than IgE – ADA + patients. This work provides evidence that IFX-specific circulating T cells are detectable mainly in ADA + patients with HRs, regardless of their disease. The IFX-induced cytokine pattern partially correlates with the ADA isotype. Graphical Abstract: